Puesta a punto de la embotelladora didáctica de la Universidad de América (2024)
The present degree project focuses on the development of the bottling machine proposed in the thesis “Design and technological development of an educational packaging equipment for the production control laboratory of the Universidad de América Foundation” [1], prepared in 2018 by Jeison Palacios and Angie Salinas; to later be intervened by the company Ingenium. When carrying out an initial analysis of the system, it was determined that it was not in the necessary conditions for its operation, which is why the starting point is a characterization of the initial operation of the bottling machine, in addition to making the different plans that cover the operation sequence of each of the components; and a diagnosis for each of the areas of the equipment, which are segregated by the type of process they carry out. This is done in order to identify the problems that must be solved.